2015
DOI: 10.1080/15384101.2015.1046647
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of insulin degrading enzyme activity and liver cell proliferation

Abstract: Diabetes mellitus type 2 (T2DM), insulin therapy, and hyperinsulinemia are independent risk factors of liver cancer. Recently, the use of a novel inhibitor of insulin degrading enzyme (IDE) was proposed as a new therapeutic strategy in T2DM. However, IDE inhibition might stimulate liver cell proliferation via increased intracellular insulin concentration. The aim of this study was to characterize effects of inhibition of IDE activity in HepG2 hepatoma cells and to analyze liver specific expression of IDE in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 26 publications
7
34
0
Order By: Relevance
“…Thus, our findings suggested that hyperglycemia may provoke the disturbance of IDE activity in T2DM. Moreover, we found a decrease of IDE mRNA expression in the liver of diabetic subjects (67). Further, decreased hepatic insulin degradation is an early marker of a disturbed insulin metabolism in obesity and T2DM (68,69), and prodiabetic genetic polymorphisms of the IDE gene are associated with reduced insulin clearance (56).…”
Section: Compoundmentioning
confidence: 63%
See 1 more Smart Citation
“…Thus, our findings suggested that hyperglycemia may provoke the disturbance of IDE activity in T2DM. Moreover, we found a decrease of IDE mRNA expression in the liver of diabetic subjects (67). Further, decreased hepatic insulin degradation is an early marker of a disturbed insulin metabolism in obesity and T2DM (68,69), and prodiabetic genetic polymorphisms of the IDE gene are associated with reduced insulin clearance (56).…”
Section: Compoundmentioning
confidence: 63%
“…T2DM is known to be an independent risk factor for hepatocellular carcinoma (76) possibly via chronic hyperinsulinemia. We recently found that RNAi IDE knockdown induces dysregulation of p53 pathway and an increase of proliferation markers in HepG2 hepatoma cells, although the proliferation rate was lower in IDE knockdown cells than in controls (67). Analysis of microarray datasets from liver samples of diabetic subjects revealed a decrease of IDE expression accompanied by downregulation of the p53-dependent genes FAS and CCNG2, but not by upregulation of proliferation markers (67).…”
Section: Compoundmentioning
confidence: 97%
“…Both models were accompanied by disturbances in the p53 pathway, which might affect tumorigenesis in the liver. 6 Whether this is a direct effect of IDE or mediated by changes in the proteasome-ubiquitin system is not clear. Certainly the effects of inhibition of IDE have to be carefully investigated -not only in liver, but also in other tissues, as brain and pancreatic islands -in order to make this a suitable future strategy of type 2 diabetes treatment.…”
mentioning
confidence: 99%
“…Likewise, other authors found a decrease of Ide mRNA expression in the liver of diabetic subjects [184].…”
Section: Ide and Diabetes Mellitusmentioning
confidence: 73%
“…Some of these authors report increased IDE levels in plasma and human erythrocytes of T2DM patients, both in insulin-and non-insulin dependent patients [180] and [181]. In contrast, other studies reported low IDE expression in other tissues from diabetic patients, such as adipocytes [182] and liver [184]. There is a single study in the literature that reports IDE levels in pancreatic islets of diabetic patients.…”
Section: Differential Ide Expression In Pancreatic Islet Cellsmentioning
confidence: 99%